Resistance training and ursolic acid consumption affect hepatokines in aged diabetic rat liver - Zahra Hemati Farsani; Mohammad Faramarzi; Zeinab Gorgin Karaji; Hamid Akbarzadeh; Masoumeh Hossein Zadeh (Scientific Reports)
Abstract Hepatokines play an important role in age-related metabolic disorders for example diabetes. The study҆s aim is to find how resistance training and supplementation of UA affect the levels of Hepatokines in the liver tissue of male Wistar rats that were treated with STZ and were of advanced age. Twenty-five 21-month-old male rats were randomly assigned to five equal groups: healthy control (HC), diabetic with uric acid supplementation (DU), supplementation plus resistance exercise (DRU), resistance exercise only (DR) and diabetic control (DC).The resistance training protocol was performed for 8 weeks, with 60% of the maximum voluntary contraction capacity (MVCC), climbing the ladder 14–20 times, 5 days a week. Rats were given a combination of high-fat food and 500 mg/kg of UA. Consistent with the results of one-way ANOVA, the decrease in ANGPTL6 in the DU and DR groups compared to the DCgroup is significant (p ≤ 0.05), while the decrease in the DRU group compared to theDU group was not significant (p ≥ 0.05). Fetuin Adecreased significantly (p ≤ 0.05) in the DU group compared to the DC group, but did not change significantly (p ≥ 0.05) in the DR and DRU groups. According to the results of one-way ANOVA, the decrease in FETUB, Hepassocin, LECT2, and Selenoprotein is significant in all groups (p ≤ 0.05). Based on the beneficial effects of resistance training and UA supplementation on glucose metabolism and Hepatokines, it appears that the blend of exercise training and UA supplementation has a more effective therapeutic effect on hepatic Hepatokines in elderly individuals with diabetes.